Teach like a champion 3.0 : 63 techniques that put students on the path to college - Lemov, Doug, 1967- (Hoboken, NJ : Jossey-Bass, a Wiley imprint, 2021)
Teach Like a Champion 3.0 is the revised, expanded, and up-to-date revision of Doug Lemov's study of the craft of teaching. Upon studying videos of high-performing teachers, Lemov distills their methods into concrete tangible actions for others to use and adapt. Many of the techniques he describes are now part of the lingua franca of teaching, but here Lemov adds the results of his last five years of study, including new depth and detail to existing techniques and the addition of more than ten new techniques. Through the techniques, Lemov explains how to Check for Understanding, raise academic expectations, increase the ratio of the cognitive work students do,motivate and engage students, make classrooms more writing-intensive, improve discussions, and anticipate when it is necessary to redirect student behavior so it is positive and productive. Int his edition, Lemov adds extensive discussions of the research connecting the techniques more explicitly to cognitive and social sciences. He also updates his discussion based on extensive reflections on issues in Diversity, Equity, and Inclusion. These additions will help teachers to be clear on the why and the how behind their teaching decisions.
Five themes: mental models and purposeful execution -- Lesson preparation -- Check for understanding -- Academic ethos -- Lesson structures -- Pacing -- Building ratio through questioning -- Building ratio through writing -- Building ratio through discussion -- Procedures and routines -- High behavioral expectations -- Building student motivation and trust.
Includes bibliographical references and index.
Keywords: Didactiek; Didactische principes; Didactische werkvormen; Feedback; Hoge verwachtingen; Leerproces; Motivatie